Middle class families : social and geographical mobility - Bell, Colin, 1942- (International library of sociology. Sociology of gender and the family, 1998)
Sociologists have continued to monitor the effect of women's changing roles on their children and families as their employment opportunities have increased and got better. They also experimented with social behaviour and roles of women today.